Strengthening governance in higher education: The role of internal audit as the third line of defense - Rumiyati, Rumiyati; Nusa, Nabella Duta (JIFA (Journal of Islamic Finance and Accounting), 2024)
This study examines the internal audit functions at four universities, both public and private, in the Special Region of Yogyakarta, Indonesia, with a focus on their contribution to governance and their role as the organization's third line of defense, as recommended by The Institute of Internal Auditors. Employing a qualitative research approach, the study utilizes descriptive data analysis to assess the effectiveness of internal audits in these institutions. The findings reveal that while the internal audit functions in both state and private universities receive adequate organizational support, they face resource constraints, particularly in state universities that are not yet legally incorporated and private universities with newly established audit functions. The study also highlights the diversity of audit activities, including review and consultation, with more established internal audit units demonstrating greater variety and depth in their assignments. Moreover, the internal audit function emerges as a strategic partner in risk management, effectively serving as the third line of defense through regular coordination and communication with university management. This research underscores the critical role of internal audits in enhancing governance and managing risks within the higher education sector.